'Kevin Vallier' Trust in a Polarized Age - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2023)
Vallier offers a defence of liberalism that is publicly justified as an answer to political polarization. This critique argues that the philosophical solution he offers - a version of liberalism more likely to be endorsed by moderately idealized agents - may not succeed because the source of polarization lies elsewhere: in resentments arising out of changed social conditions and the alienation of parts of society unhappy with the very liberal narrative in question.